Pathophysiological Features Of Hemostatic Disorders In Infants With Acute Pneumonia Complicated By Perinatal Cns Injury (Texas Journal of Medical Science, 2025)
Acute pneumonia is one of the leading causes of morbidity and mortality in infants, with disease severity markedly increasing in those with perinatal central nervous system (CNS) injury. Hypoxic - ischemic encephalopathy, traumatic brain injury, and perinatal asphyxia create persistent endothelial dysfunction and impaired neurohumoral regulation, predisposing infants to exaggerated inflammatory and prothrombotic responses during respiratory infections. Understanding the pathophysiological mechanisms of hemostatic disturbances in this vulnerable population is crucial for improving early diagnosis, therapeutic strategies, and clinical outcomes.